Vacating place, vacated space? A research agenda for places where people leave - Koning JD; Hobbis SK; McNeill J; Prinsen G (Elsevier Ltd, 2021)
What happens to rural places when people leave? We propose a research agenda that accounts for the material and immaterial values of depopulating and depopulated places. A three-pronged research framework departing from the notion of place is outlined that focuses on the social and political relations and the natural environment in which vacating places are embedded. We use vignettes of places in Ecuador, New Zealand and the Autonomous Region of Bougainville of Papua New Guinea to illustrate how this framework can be used to explore how depopulation has transformed the sense of place. Each explores an aspect of this transformation: (1) replacing people – where inhabitants of a place are replaced; (2) diluting local voice – where the local sense of place is diluted through changing governance arrangements through institutional amalgamation; and (3) transforming nature – where the biophysical transformation of a space effectively renders it inhabitable. Each vignette answers questions about who speaks for, who benefits from, and what is valued about this place. By paying close attention to political, economic, and environmental transformations and what they mean for the values of these depopulating rural areas as well as by showcasing different modes of vacating space and the consequences on legitimacy and beneficiaries, we highlight the importance of this research framework for global public policy and its applicability for both the Global North and the Global South.
Keywords: Place; Depopulation; People; Nature; Space; Governance; 1205 Urban and Regional Planning; 1604 Human Geography; 1608 Sociology